Guardians of the Forest Floor: Learning Conservation from the Asian Forest Tortoise (Manouria emys) - Pratama, Ariyoga; Ruyani, Aceng (SEAMEO BIOTROP, 2026)
Deep within the tropical forests of Southeast Asia, the Asian forest tortoise (Manouria emys) moves with the quiet memory of millions of years. Yet today, its path is threatened by deforestation, illegal trade, and a warming climate. In Bengkulu, Indonesia, the University of Bengkulu’s ex-situ program has successfully increased the survival and breeding success of rescued tortoises, providing controlled habitats where health, behavior, and reproduction can be monitored. Supported by collaboration with the University of North Carolina Greensboro, the program rehabilitates confiscated individuals and prepares them for long-term population recovery. Beyond protecting a species, this initiative transforms conservation into education, where the tortoise becomes a living teacher of patience, empathy, and coexistence.